Integrated teaching-assessment-learning planning: perspectives in construction (Revista Contexto & Educação, 2025)
The aim of this paper was to analyze the perceptions of Biological Sciences pre-service teaching undergraduate students on the theoretical-practical foundations of the Integrated Teaching-Assessment-Learning Planning, after training meetings held within the scope of the Supervised Curricular Internship. The qualitative research of an interpretative nature was carried out with 12 students from the Biological Sciences Teaching Degree course at a public university in the state of Paraná, Brazil. Data was constructed from questionnaires and activities organized during the training practice carried out with the participants. To analyze these data, we opted for the Discursive Textual Analysis methodology, which was appropriate for the interpretation of the statements, which were organized into categories and subcategories that reveal the reflections built from the theoretical-practical foundations of the Integrated Teaching-Assessment-Learning Planning. Those relating to the act of didactically planning the teaching, assessment and learning processes, in an integrated manner, stood out, contributing to coherent, planned and reflective actions on the role of planning and assessment in pedagogical practice.
Keywords: teacher education; biological sciences; formative assessment